2012
DOI: 10.5505/tjtes.2012.47639
|View full text |Cite
|
Sign up to set email alerts
|

Pellet gunfire injuries among agitated mobs in Kashmir

Abstract: AMAÇAyaklanan grupların kontrol edilirken uğradıkları saçma ile silah yaralanmaları incelendi. GEREÇ VE YÖNTEMSaçma tanesi ile gerçekleşen silah yaralanmaları nedeniyle kaza ve acil servis bölümüne yatırılan toplam 198 hasta, anatomik bölge, ciddiyet ile yaralanma tipi, tedavi ve sonuçlar bakımından değerlendirildi. BULGULARHastaların %72,7'si, 16 ile 25 yaş arasında idi. En sık yaralanma bölgeleri ekstremiteler (%47,9), karın (%36,3) ve göğüs (%31,3) idi. Hastaların %59,5'inde minör yaralanma vardı. Yaralanma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 13 publications
3
22
1
Order By: Relevance
“…16 At this velocity pellets can easily damage eyes and penetrate skin to damage deeper structures. Hence patients with pellet injuries should be evaluated for deeper injuries.…”
Section: Discussionmentioning
confidence: 99%
“…16 At this velocity pellets can easily damage eyes and penetrate skin to damage deeper structures. Hence patients with pellet injuries should be evaluated for deeper injuries.…”
Section: Discussionmentioning
confidence: 99%
“…6/30 patients (20%) in our study had negative exploration. Majid mushtaque et al [3] in their study also had negative laparotomy in 4 patients with pellet injuries to abdomen. Delayed laparotomy was done in3/20 patients in our study while as 17/20 patients did well with conservative management despite CECT showing multiple pellets in the parietal wall, presence of Pneumoperitoneum and pellets in bowel lumen Figure 3(d).…”
Section: Discussionmentioning
confidence: 99%
“…Bond et al [7] and Majidmushtaque et al [3] also reported that small bowel is the most frequently injured viscera in pellet injuries to abdomen and multiple bowel perforations being the common intra-operative finding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The modern high-powered rifles can propel a pellet beyond 1100 ft/s (330 m/s), approximately the speed of sound, and produce a noise similar to a 22-calibre rim fire rifle [1,2]. They can generate muzzle velocities of 350 ft/s or more.…”
Section: Introductionmentioning
confidence: 99%